2021
DOI: 10.1017/s1041610221000120
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal microbiota as a predictor for antidepressant treatment outcome in geriatric depression: a prospective pilot study

Abstract: Objectives: (1) To investigate if gut microbiota can be a predictor of remission in geriatric depression and to identify features of the gut microbiota that is associated with remission. (2) To determine if changes in gut microbiota occur with remission in geriatric depression. Design: Secondary analysis of a parent randomized placebo-controlled trial (NCT02466958). Setting: Los Angeles, CA, USA (2016-2018) Participants: Seventeen subjects with major d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Participants were recruited from geriatric ambulatory care settings (UCLA Geriatric Medicine-Psychiatry clinics) and from local advertisements to participate in the parent clinical trial of levomilnacipran for geriatric depression (NCT 02466958) that was previously reported elsewhere [ 27 , 49 ]. Of 29 randomized patients, 16 older adults (37.5% female; mean age, 70.6 (SD = 5.7) years; Table 1 ) completed both MRI and stool sample collection and were included in this report.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were recruited from geriatric ambulatory care settings (UCLA Geriatric Medicine-Psychiatry clinics) and from local advertisements to participate in the parent clinical trial of levomilnacipran for geriatric depression (NCT 02466958) that was previously reported elsewhere [ 27 , 49 ]. Of 29 randomized patients, 16 older adults (37.5% female; mean age, 70.6 (SD = 5.7) years; Table 1 ) completed both MRI and stool sample collection and were included in this report.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the existing neuroimaging data, an emerging and promising area of biological GD mechanisms is that of gut microbiota [ 27 ]. The gut microbiota, as the largest reservoir of microbes in the human body, have an essential role in the central nervous system (CNS) functioning through the bidirectional gut–brain axis [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond diagnostic and prediction of diseases, the gut microbiome data could also be useful in the prediction of responsiveness to treatment in multiple age-related diseases. For instance, a recent prospective pilot study has shown that the microbial taxonomic composition of elderly with geriatric depression may be indicative of their response to antidepressants [ 134 ]. In another study, the baseline composition of the fecal microbiome, particularly the relative abundance of Faecalibacterium prausnitzii , was used to predict whether Crohn’s disease patients would experience a clinical relapse following discontinuation of immunosuppressive therapy [ 135 ].…”
Section: Perspectives Opportunities and Challenges In The Research Of...mentioning
confidence: 99%
“…Jin M et al found that Prevotella.9 were signi cantly decreased in patients with positive immune antibodyassociated recurrent abortion [28]. The enrichment of Faecalibacterium, Agathobacter and Roseburia were related to geriatric depression [35].…”
Section: Rsa Patients Have Abnormal Gut Microbiotamentioning
confidence: 99%